Klasyfikacja województw według zróżnicowania dochodowego, wydajności pracy, zmian struktury sektorowej oraz migracji ludności - Batóg, Jacek (The Classification of Voivodeships According to the Income Inequality, Productivity, Changes of the Sectoral Structure and Migrations, 2008)
In the article the author tries to classify voivodeships in the dependence of the crucial factors influencing the scale of regional income inequalities. One reckones their productivity, the concentration of the economic activity and the structural changes of the economy. As a result of used agglomeration procedure there was obtained the partition of voivodeships on three groups: central, peripheric and neutral. The received results show also on the occurrence of significant migrations of the population from peripheric to central voivodeships.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 485-492